Electronic properties of Pu19Os simulating β-Pu: the strongly correlated Pu phase. (1st February 2018) - Havela, L; Mašková, S; Kolorenč, J; Colineau, E; Griveau, J-C; Eloirdi, R
Abstract: We established the basic electronic properties of ζ-Pu19 Os, which is a close analogue to β-Pu, and its low-temperature variety, η-Pu19 Os. Their magnetic susceptibility is 15% higher than for δ-Pu. A specific heat study of ζ-Pu19 Os shows a soft lattice similar to δ-Pu, leading to a low Debye temperature Θ D   =  101 K. The linear electronic coefficient γ related to the quasiparticle density of states at the Fermi level points to a higher value, 55  ±  2 mJ (mol Pu K 2 ) –1, compared to 40 mJ (mol K 2 ) –1 for δ-Pu. The results confirm that β-Pu is probably the most strongly correlated Pu phase, as had been indicated by resistivity measurements. The volume and related Pu–Pu spacing is clearly not the primary tuning parameter for Pu metal, as the β-Pu density stands close to the ground-state α-phase and is much higher than that for δ-Pu. The η-Pu19 Os phase has a record γ -value of 74  ±  2 mJ (mol Pu K 2 ) –1 . The enhancement is not reproduced by LDA+DMFT calculations in the fcc structure, which suggests that multiple diverse sites can be the key to the understanding of β-Pu.